Microtargeting the Market: A Bibliometric Mapping of Digital Marketing Trends in Entrepreneurship - Judijanto, Loso; Souisa, Wendy; Lussy, Kalsum; Tetelepta, Maria Marlyn; Tutupoho, Fauzia (Westscience Press, 2025)
This study presents a bibliometric mapping of digital marketing trends in entrepreneurship, with a focused lens on the emergence and role of microtargeting strategies. By analyzing 2000–2025 publications sourced from the Scopus database, the study uncovers the intellectual structure, thematic evolution, and global collaboration patterns within this interdisciplinary research domain. Using VOSviewer for keyword co-occurrence, co-authorship, institutional, and country-level analyses, the study reveals that core themes such as entrepreneurship, social media, innovation, digital transformation, and marketing strategy dominate scholarly discourse. The findings also show that countries like India, Indonesia, the United States, and the United Kingdom lead in collaborative research output. Co-citation mapping highlights the convergence of foundational theories in marketing and entrepreneurship, while the overlay and density visualizations suggest a temporal shift toward personalized, data-driven marketing practices post-2021. The study contributes theoretically by identifying underexplored research gaps and practically by guiding entrepreneurs and institutions toward effective microtargeting strategies. Limitations and directions for future research are also discussed to advance the field further.